2015
DOI: 10.1080/00224499.2014.1002556
|View full text |Cite
|
Sign up to set email alerts
|

A Swiss Longitudinal Study of the Prevalence of, and Overlap Between, Sexual Problems in Men and Women Aged 20 to 50 Years Old

Abstract: The aim of this study was to obtain data on the development and course of sexual problems and their interrelationships by investigating a representative sample of men and women over a period of 30 years. A representative sample of 299 women selected from the complete electoral register and 292 men selected from screening lists for military service in Zurich, Switzerland, answered questions about their sexuality as part of a series of seven interviews between ages 20 (1979) and 50 (2008). Of the initial sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 59 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Psychiatric constructs and incidence rates vary by culture and region, but worldwide the global disease burden of mental illness is a "distant first" in terms of disability-adjusted life years and represents 32.4% of the burden of years lived with disability according to several analyses (Vigo et al 2016). The prospective Zurich cohort study found that the chance to experience any mental disorder from ages 20 to 50 was 73.9% (Angst et al 2015). Of these mental disorders, it is generally accepted that approximately 30% will be substance use disorders, 15% anxiety disorders, 10% depression or mood disorders, 5% attentional/executive function disorders, 2% bipolar depression, and 1% schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric constructs and incidence rates vary by culture and region, but worldwide the global disease burden of mental illness is a "distant first" in terms of disability-adjusted life years and represents 32.4% of the burden of years lived with disability according to several analyses (Vigo et al 2016). The prospective Zurich cohort study found that the chance to experience any mental disorder from ages 20 to 50 was 73.9% (Angst et al 2015). Of these mental disorders, it is generally accepted that approximately 30% will be substance use disorders, 15% anxiety disorders, 10% depression or mood disorders, 5% attentional/executive function disorders, 2% bipolar depression, and 1% schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have examined changes in sexual desire are diary studies focusing on daily fluctuations (e.g., Muise, Impett, Kogan, & Desmarais, 2013), cross-sectional studies (e.g., Sprecher & Regan, 1998), or studies that focused on sexual dysfunctions (e.g., Angst, Hengartner, R€ ossler, Ajdacic-Gross, & Leeners, 2015) or desire at middle age (e.g., H€ allstr€ om & Samuelsson, 1990). Other studies looked at constructs related to sexual desire (i.e., sexual frequency and sexual satisfaction; McNulty, Wenner, & Fisher, 2016), but did not directly consider factors that moderate the trajectory of desire over relationship development.…”
mentioning
confidence: 99%